2015
DOI: 10.4103/2249-4863.154661
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced hepatitis and the risk factors for liver injury in pulmonary tuberculosis patients

Abstract: Introduction:Short-course chemotherapy containing rifampicin and isoniazid in combination has proved to be highly effective in the treatment of tuberculosis, but one of its adverse effects is hepatotoxicity. Various risk factors have been found to be associated with drug-induced liver injury (DILI) in general population. The study aimed to determine the prevalence of drug-induced hepatitis and the risk factors associated with the DILI among the patients of pulmonary tuberculosis in Indian patients.Setting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 20 publications
(23 reference statements)
6
45
4
3
Order By: Relevance
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are comparable with results of other investigator who found that the onset of DILI ranged from 13 days to 58 days (median, 26 days) after initiation of treatment [36]. And in another study, the median latent period for developing DILI was found to be 19 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] days [37].…”
Section: Discussionsupporting
confidence: 82%
“…In another study, It was as low as 3.8% in cohort study of 3900 patients and only 150 had DILI but only 2 patients had hepatitis B surface Antigen positive [19], while in our study 76% DILI were seen in hepatitis co infection patients and 24% in non hepatitis infection. Recently the incidence of DILI has reduced to about 8%-10% in developing countries but it ranges from 1%-3.3% in Western countries [25].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Hepatotoxicity, which is a known adverse effect of systemic Rifampicin therapy at a dose of 600 mg per day,19,20 was not seen in any of our patients having daily dose of 300mg. Liver function tests which were performed before and during the follow up period remained within normal range.…”
Section: Discussionmentioning
confidence: 53%
“…Drug induced liver injury (DILI) has been regarded as a potential side effect of Rifampicin. The mechanism involved is oxidative stress induced by Rifampicin that leads to hepatocyte injury and raised liver enzymes in serum 19,20…”
Section: Discussionmentioning
confidence: 99%